1988
DOI: 10.3354/meps045087
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between polyps of Aurelia aurita and planktonic larvae of scyphozoans: an experimental study

Abstract: Predation by polyps of the scyphozoan Aurelia aurita (L.) on planula larvae of their own species and on planulae of the scyphozoan Cjfanea capillata (L.) was studied in laboratory experiments.Transplant experiments in the field tested whether high densities of established A. aurita polyps could affect the recruitment of planktonic larvae and if Interactions between the polyps occur. More planula larvae of C. caplllata than of A. aurita were eaten by the polyps. The transplant experiments showed that dense cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 18 publications
2
35
1
Order By: Relevance
“…2). These results contradict a previous study (Grondahl 1988b) which showed that even a low density of 100 established polyps (10-d old) can reduce the settling of new planula larvae (Fig. 3).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…2). These results contradict a previous study (Grondahl 1988b) which showed that even a low density of 100 established polyps (10-d old) can reduce the settling of new planula larvae (Fig. 3).…”
Section: Discussioncontrasting
confidence: 56%
“…The difference between the 2 studies is the duration of the transplant experiments. In the present study 4-d old established polyps were transplanted to the field for 4 d, while in Grondahl (1988b) polyps were transplanted to the field for 10 d. In the latter study, competition for food or space may have developed among the established polyps and they were also more than twice as large as in the present study (0.62 mm and 0.28 mm, respectively). In Grondahl (1988b) the established polyps also had welldeveloped feeding devices (tentacles), whereas this was not the case with the 4-d old polyps used in the present study (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The reproduction and mortality of A.aurita in the polyp stage may have considerable influence on the population size of the medusa [1,8]. Gröndahl suggested that planula and polyp mortality rates influence the medusa population more than ephyra and medusa mortality rates [9]. Biological methods to preserve the environment such as eutrophication treatment are suggested [10].…”
Section: Introductionmentioning
confidence: 99%